FEATURES OF USING SMM FOR EFFECTIVE MANAGEMENT OF RESTAURANT BUSINESS ENTERPRISES - TOMALIA, TATIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights the problem of using social networks, which is due to the active development of marketing, both worldwide and in Ukraine. Competition in the global market is intensifying, and therefore companies need to spend more money to promote their product so that it is not lost among many others. At the same time, the pandemic caused by Covid-19 has reduced marketing budgets. However, there is a growing need to find cost-effective and efficient ways to communicate with consumers. Businesses are encouraged to pay special attention to Internet marketing tools that promote the restaurant product, the restaurant business itself, and its brand through using social media, the content of which is created or updated through the efforts of owners and visitors, namely social media marketing. Competition is also intensifying, so only those companies that know and understand their consumers and competitors well, pursue effective communication policies, will succeed in the market. The shift of interests from mass to targeted marketing, as well as the dynamic development of communication channels and promotion tools have set new challenges for marketers. The article examines the existing methods of SMM promotion for use in the restaurant business, among which were targeted advertising, SEO promotion, interaction with users, competitions, advertising in communities. The main tasks of SMM, its advantages/disadvantages were highlighted. The main attention was paid to the method of evaluating the effectiveness of promotion and communication effectiveness of SMM for restaurant businesses. Several measures for the effective implementation of SMM in restaurants are proposed.